To Explore The Mode Of Action Of Kshara Basti In Medoroga w.s.r. To Dyslipidemia - Sharma, Santvana; Saroj, Udai Raj; Joshi, Ram Kishor (International Research Journal of Ayurveda & Yoga, 2021)
Dyslipidemia, defined as high total or LDL cholesterol levels or low HDL cholesterol levels, is a major risk factor for CHD and stroke (cerebrovascular disease). Dyslipidemia is caused by causative factors such as high fat diet and sedentary lifestyle, which can be compared to Ahara having Snigdha, Guru, Picchila, Sheet Guna, and Chestha Dvesha (lack of exercise), which lead to Kapha and Medo Dosha Vridhi (Gunataha Vridhi), that can be correlated to Medodosha and subsequently as Medoroga. As a result, Medoroga can be classified as “Santarpannimittajvikara” (diseases due to over nutrition). Aptarpana is one of the key therapeutic treatment of Santarpana Nimittaja Vyadhi. Basti that falls under Yuktivyapashraya Chikitsa, has Achintya Shakti, and is referred to in Ayurvedic scriptures as Ardhachikitsa. Basti prepared with Aptarpaka Dravya (medicated enema) is beneficial in eradicating vitiated Doshas and eliminating obstructions in Srotasa, eliminating Ama (harmful metabolites) from the body, and interrupting disease propagation. Because of its direct influence on Pakvashaya (Vata Sthana), Basti may be the most effective therapy procedure for correcting Medavrita Vata Dosha, which is the primary factor involved in the pathophysiology of Medoroga. Therefore, Basti with contents Haridra, Daruharidra, Triphala, Musta, Shyonaka with Yavakshara, Gomutra, Madhu and less amount of Sneha, described for treatment in Kaphaja Roga by Acharya Charaka is taken for review.